Spatial Positioning and Matrix Programs of Cancer-Associated Fibroblasts Promote T-cell Exclusion in Human Lung Tumors - Grout, John A.; Sirven, Philemon; Leader, Andrew M.; Maskey, Shrisha; Hector, Eglantine; Puisieux, Isabelle; Steffan, Fiona; Cheng, Evan; Tung, Navpreet; Maurin, Mathieu; Vaineau, Romain; Karpf, Lea; et al. (Cancer discovery, 2022)
It is currently accepted that cancer-associated fibroblasts (CAF) participate in T-cell exclusion from tumor nests. To unbiasedly test this, we used single-cell RNA sequencing coupled with multiplex imaging on a large cohort of lung tumors. We identified four main CAF populations, two of which are associated with T-cell exclusion: (i) MYH11+αSMA+ CAF, which are present in early-stage tumors and form a single cell layer lining cancer aggregates, and (ii) FAP+αSMA+ CAF, which appear in more advanced tumors and organize in patches within the stroma or in multiple layers around tumor nests. Both populations orchestrate a particular structural tissue organization through dense and aligned fiber deposition compared with T cell-permissive CAF. Yet they produce distinct matrix molecules, including collagen IV (MYH11+αSMA+ CAF) and collagen XI/XII (FAP+αSMA+ CAF). Hereby, we uncovered unique molecular programs of CAF driving T-cell marginalization, whose targeting should increase immunotherapy efficacy in patients bearing T cell-excluded tumors. The cellular and molecular programs driving T-cell marginalization in solid tumors remain unclear. Here, we describe two CAF populations associated with T-cell exclusion in human lung tumors. We demonstrate the importance of pairing molecular and spatial analysis of the tumor microenvironment, a prerequisite to developing new strategies targeting T cell-excluding CAF. See related commentary by Sherman, p. 2501. This article is highlighted in the In This Issue feature, p. 2483.